Seismic performance of reinforce concrete buildings designed according to codes in Bangladesh, India and U.S. (1st April 2018) - Mostafijur Rahman, Muhammad; Jadhav, Sagar M.; Shahrooz, Bahram M.
Highlights: Seismic building codes in Bangladesh, India, and the U.S. are compared and evaluated. The similarities and differences of these codes are presented. A12-story building located in high seismic regions of these countries is designed. Nonlinear response history analyses of the buildings are conducted. Different metrics are used to examine the performance of the buildings. Abstract: This paper focuses on the comparison of seismic design provisions in Bangladesh (BNBC-1993), India (IS-1893), and the U.S. (ASCE 7-10) in relation to analysis, design, and seismic performance of reinforced concrete buildings on the basis of the type of allowable analysis procedures, zoning system, site classification, fundamental vibration period of the structure, response reduction factor, importance factor, minimum design lateral force, allowable story drifts, and design response spectra. Three geometrically similar commercial reinforced concrete buildings in high seismic regions of Bangladesh, India, and U.S. were designed and detailed per the respective codes. Three-dimensional nonlinear dynamic analyses of the designed structures were conducted. Each structure was subjected to a pair of orthogonally applied artificial ground motions compatible with the design response spectrum for each building code. The structural performance of each building was compared in terms of roof displacements, inter-story drifts, load-carrying capacity of beams and columns, and overall energy dissipation characteristics. The comparisons allowed an in-depth evaluation of the differences in the seismic performance of buildings designed according to ASCE 7-10, BNBC-1993, and IS-1893 codes. The Indian code performed better when subjected to the ground motion that is intended to represent the Indian design response spectrum.